Pr ion doped gallate laser crystal material and preparation method and application thereof

By preparing Pr ion doped gallate laser crystals, the disordered structure enhances the absorption and emission of Pr ions, the problems of difficulty in growing existing laser crystals and poor thermal mechanical properties are solved, and the visible-band laser output with high output power is achieved .

CN119221128AActive Publication Date: 2024-12-31JIANGXI UNIV OF SCI & TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411333337.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-31
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing Pr ion-doped laser crystals have difficulty in growing and poor thermal mechanical properties, which limit the increase in the visible band laser output power under blue light LD pump.

Method used

The gallate laser crystal material with Pr ion doped is prepared by two sintering and lifting growth methods to form a disordered structure xPr:AB1-xGa3O7 crystal, which enhances the absorption and emission intensity of Pr ions and achieves high output power. Visible light band laser.

Benefits of technology

The output of cyan, orange and red lasers with high output power under direct pumping of blue light LD is achieved, and the crystals have good physical and chemical stability and thermal properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221128A_ABST
    Figure CN119221128A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of inorganic laser materials, and particularly relates to a Pr ion doped gallate laser crystal material and a preparation method and application thereof. The chemical formula of the Pr ion doped gallate laser crystal material provided by the invention is shown as a formula 1: xPr: AB1-xGa3O7 formula 1, in the formula 1, an element A is at least one of Ca, Sr and Ba, an element B is at least one of Y, La, Gd and Lu, and x is greater than 0 and less than or equal to 0.2. The Pr ion-doped gallate laser crystal material provided by the invention is a single crystal material, and can enhance the absorption and emission intensity of Pr ions according to the disordered structure of the host crystal, so that more efficient laser output is realized when the crystal is directly pumped by a blue light LD (laser diode). The crystal provided by the invention can be used for laser output of a visible light band, and has a wide application prospect in the fields of scientific research, industrial manufacturing and military affairs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic laser materials, and in particular relates to a Pr ion-doped gallate laser crystal material and a preparation method and application thereof. Background Art

[0002] Lasers in the visible band of 400 to 760 nm are the basic light sources in the fields of storage, display, processing and communication. As a typical representative of rare earth ions, Pr ion-doped laser crystals can achieve absorption in the blue light region and multi-wavelength emission from green to red light bands. They are an important blue-light-pumped all-solid-state visible-band laser material. At present, Pr ion-doped laser crystals are mainly concentrated in halide crystals represented by fluorides. The crystals have shortcomings such as difficulty in growth and poor thermal mechanical properties of the crystals themselves, which restricts its application development. It is imperative to find oxide crystals that are simple to grow and have good mechanical properties.

[0003] With the substantial increase in the output power of blue light InGaN semiconductor lasers (LDs), a method of directly outputting visible-band lasers by pumping Pr ion-doped oxide laser crystals with blue light LDs has attracted the attention of researchers. At present, blue light LD pumping has been successfully used in Pr:YAlO3, Pr:Y3Al5O 12 、Pr:SrAl 12 O 19 Laser output has been achieved in oxide crystals, but the output power is low (less than 1W) and needs to be further improved. Summary of the invention

[0004] The purpose of the present invention is to provide a Pr ion-doped gallate laser crystal material, a preparation method and an application thereof. The Pr ion-doped gallate laser crystal material provided by the present invention can enhance the absorption and emission intensity of Pr ions according to the disordered structure of the matrix crystal itself, so that when the crystal is directly pumped by a blue light LD, it can achieve laser output in the visible light band with high output power.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a Pr ion-doped gallate laser crystal material, the chemical formula of the Pr ion-doped gallate laser crystal material is shown in Formula 1:

[0007] xPr:AB 1-x Ga3O7 formula 1,

[0008] In Formula 1, the A element is at least one of Ca, Sr and Ba, the B element is at least one of Y, La, Gd and Lu, and 0<x≤0.2.

[0009] Preferably, the Pr ion-doped gallate laser crystal material belongs to the tetragonal system, and the space group is

[0010]

[0011] Preferably, the A element is Ca or Sr, and the B element is Gd or La.

[0012] The present invention provides a method for preparing the Pr ion-doped gallate laser crystal material described in the above technical solution, comprising the following steps:

[0013] According to the chemical composition of the Pr ion-doped gallate laser crystal material, the prepared raw material is sintered twice to obtain xPr:AB 1-x Ga3O7 polycrystalline raw material; the two sinterings include a first sintering and a second sintering;

[0014] In a protective gas atmosphere, the xPr:AB 1-x The Ga3O7 polycrystalline raw material is pulled and grown to obtain the Pr ion-doped gallate laser crystal material.

[0015] Preferably, the preparation raw materials include praseodymium oxide, gallium oxide, a carbonate containing element A and an oxide containing element B.

[0016] Preferably, the first sintering comprises sequentially performing a first grinding, a first tableting and a first calcining;

[0017] The temperature of the first calcination is 1000-1300° C., the time is 15-25 hours, and the heating rate from room temperature to the temperature of the first calcination is 150-250° C. / h.

[0018] Preferably, the second sintering comprises sequentially performing a second grinding, a second tableting and a second calcining;

[0019] The temperature of the second calcination is 1000-1300° C., the time is 15-25 hours, and the heating rate from room temperature to the temperature of the second calcination is 150-250° C. / h.

[0020] Preferably, the pulling growth temperature is 1500-1700° C., the pulling speed is 0.5-3 mm / h, and the rotation speed is 5-15 r / min.

[0021] Preferably, after the pulling growth is completed, an initial crystal is obtained, which further includes: cooling the initial crystal from the pulling growth temperature to room temperature to obtain the Pr ion-doped gallate laser crystal material; the cooling rate is 5 to 20°C / h.

[0022] The present invention provides the use of the Pr ion-doped gallate laser crystal material described in the above technical solution or the Pr ion-doped gallate laser crystal material prepared by the preparation method described in the above technical solution in laser output in the visible light band.

[0023] The present invention provides a Pr ion-doped gallate laser crystal material, the chemical formula of the Pr ion-doped gallate laser crystal material is as shown in Formula 1: xPr:AB 1-x Ga3O7 formula 1, wherein: element A is at least one of Ca, Sr and Ba, element B is at least one of Y, La, Gd and Lu, 0<x≤0.2. The Pr ion doped gallate laser crystal material (chemical formula xPr:AB 1-x Ga3O7, referred to as Pr:ABGM) is a new type of gallate laser matrix material, in which the A element, i.e., divalent alkaline earth cations (at least one of Ca, Sr and Ba) and the B element, i.e., trivalent rare earth cations (at least one of Y, La, Gd and Lu), belong to the same 4e lattice site. During growth, the A atoms and the B atoms will occupy each other to a certain extent (i.e., mixed occupation), resulting in a disordered crystal structure, which will enhance the absorption and emission intensity of the Pr ions, and make the absorption peak and emission peak of the Pr ions broaden to a great extent, which is very suitable for blue light LD pumping to achieve cyan, orange and red laser output. At the same time, the value of x in the chemical formula of the Pr ion-doped gallate laser crystal material provided by the present invention varies between 0 and 0.2 according to the needs of laser operation, and has good physical and chemical stability, good thermal properties and low phonon energy. In summary, the Pr ion-doped gallate laser crystal material provided by the present invention is a single crystal material. According to the disordered structure of the matrix crystal itself, the absorption and emission intensity of Pr ions can be enhanced, so that the crystal can achieve laser output with high output power when directly pumped by a blue light LD.

[0024] The present invention provides a method for preparing the Pr ion-doped gallate laser crystal material described in the above technical solution, comprising the following steps: sintering the raw material twice according to the chemical composition of the Pr ion-doped gallate laser crystal material to obtain xPr:AB 1-x Ga3O7 polycrystalline raw material; in a protective gas atmosphere, the xPr:AB 1-x The Ga3O7 polycrystalline raw material is pulled and grown to obtain the Pr ion-doped gallate laser crystal material. The method provided by the present invention uses the pulling method to grow a large-sized and high-quality Pr ion-doped gallate laser single crystal material, the crystal growth method is stable, the crystal has stable physical and chemical properties and good optical properties, the raw material is easy to obtain, blue light LD can be directly used for pumping, and the output power is high.

[0025] The results of the examples show that the Pr ion-doped gallate laser crystal material provided by the present invention has 3+ ions act as activated ions to achieve 470-500nm cyan light, 590-620nm orange light, and 630-660nm red light emission. The disordered structure of the crystal enhances the Pr 3+ Absorption and emission of ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The X-ray powder diffraction patterns of the crystals obtained in Examples 1 and 2 of the present invention, and the embedded pattern is a photograph of the crystals after processing;

[0027] Figure 2 This is the absorption spectrum of the crystal obtained in Example 1 of the present invention;

[0028] Figure 3 This is the emission spectrum of the crystal obtained in Example 1 of the present invention;

[0029] Figure 4 The fluorescence decay curve of the crystal obtained in Example 1 of the present invention;

[0030] Figure 5 This is the absorption spectrum of the crystal obtained in Example 2 of the present invention;

[0031] Figure 6 This is the emission spectrum of the crystal obtained in Example 2 of the present invention;

[0032] Figure 7 The fluorescence decay curve of the crystal obtained in Example 2 of the present invention;

[0033] Figure 8 This is the X-ray powder diffraction pattern of the crystal obtained in Example 3 of the present invention, and the embedded figure is a crystal photograph;

[0034] Fig. 9 This is the emission spectrum of the crystal obtained in Example 3 of the present invention;

[0035] Fig.10 The fluorescence decay curve of the crystal obtained in Example 3 of the present invention;

[0036] Fig.11 This is the emission spectrum of the polycrystalline powder prepared in Example 4 of the present invention;

[0037] Fig.12 This is the fluorescence attenuation curve of the polycrystalline powder prepared in Example 4 of the present invention;

[0038] Fig.13 This is an emission spectrum of the polycrystalline powder prepared in Example 5 of the present invention;

[0039] Fig.14This is the fluorescence attenuation curve of the polycrystalline powder prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0040] The present invention provides a Pr ion-doped gallate laser crystal material, the chemical formula of the Pr ion-doped gallate laser crystal material is shown in Formula 1:

[0041] xPr:AB 1-x Ga3O7 formula 1,

[0042] In Formula 1, the A element is at least one of Ca, Sr and Ba, the B element is at least one of Y, La, Gd and Lu, and 0<x≤0.2.

[0043] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0044] In the present invention, in Formula 1: 0<x≤0.2, preferably 0.001≤x≤0.2. The value of x in Formula 1 varies between 0 and 0.2 according to the laser operation requirements and is not 0. The A element is preferably Ca or Sr. The B element is preferably Gd or La. Specifically, x is preferably 0.001, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1 or 0.2.

[0045] In the present invention, the Pr ion-doped gallate laser crystal material is a single crystal material, belonging to the tetragonal system, and the space group is

[0046] In the present invention, the Pr ion-doped gallate laser crystal material can achieve multiple laser outputs ranging from cyan to deep red light under 450nm blue light excitation.

[0047] The present invention provides a method for preparing the Pr ion-doped gallate laser crystal material described in the above technical solution, comprising the following steps:

[0048] According to the chemical composition of the Pr ion-doped gallate laser crystal material, the prepared raw material is sintered twice to obtain xPr:AB 1-x Ga3O7 polycrystalline raw material; the two sinterings include a first sintering and a second sintering;

[0049] In a protective gas atmosphere, the xPr:AB 1-x The Ga3O7 polycrystalline raw material is pulled and grown to obtain the Pr ion-doped gallate laser crystal material.

[0050] According to the chemical composition of the Pr ion-doped gallate laser crystal material, the raw material is sintered twice to obtain xPr:AB1-x Ga3O7 polycrystalline raw material. In the present invention, the two sinterings include a first sintering and a second sintering. The raw materials preferably include praseodymium oxide, gallium oxide, a carbonate containing element A and an oxide containing element B. The praseodymium oxide is preferably Pr6O 11 The gallium oxide is preferably Ga2O3. The carbonate containing element A preferably includes at least one of BaCO3, CaCO3 and SrCO3. The oxide containing element B preferably includes at least one of Y2O3, La2O3, Gd2O3 and Lu2O3. In a specific embodiment of the present invention, the above-mentioned raw materials are preferably prepared according to the molar ratio of each element in the chemical formula of the Pr ion-doped gallate laser crystal material.

[0051] In the present invention, the first sintering preferably includes first grinding, first tableting and first calcining in sequence. The present invention has no special requirements for the specific implementation of the first grinding and first tableting. The first calcination is preferably carried out in a muffle furnace, and the temperature of the first calcination is preferably 1000-1300°C, and specifically preferably 1200°C; the time of the first calcination is preferably 15-25h, and specifically preferably 20h; the heating rate from room temperature to the temperature of the first calcination is preferably 150-250°C / h, and specifically preferably 200°C / h.

[0052] In the present invention, after the first calcination is completed, the product obtained by the first calcination is preferably cooled to room temperature before the second sintering is performed.

[0053] In the present invention, the second sintering preferably includes a second grinding and a second tabletting in sequence. The present invention has no special requirements for the specific implementation of the second grinding and the second tabletting. The second roasting is preferably carried out in a muffle furnace, and the temperature of the second roasting is preferably 1000-1300°C, and specifically preferably 1250°C; the time of the second roasting is preferably 15-25h, and specifically preferably 20h; the heating rate from room temperature to the temperature of the second roasting is preferably 150-250°C / h, and specifically preferably 200°C / h.

[0054] In the present invention, after the second calcination, the product obtained by the second calcination is preferably cooled to room temperature to obtain xPr:AB 1-x Ga3O7 polycrystalline raw material.

[0055] Get xPr:AB 1-x After Ga3O7 polycrystalline raw materials, the present invention is in a protective gas atmosphere, the xPr:AB 1-xThe Ga3O7 polycrystalline raw material is pulled and grown to obtain the Pr ion-doped gallate laser crystal material. The present invention preferably comprises the xPr:AB 1-x The Ga3O7 polycrystalline raw material is placed in an iridium crucible and put into a pulling furnace for the pulling growth. The specific size of the iridium crucible is Φ55×50mm 3 The protective gas is preferably a non-reactive gas, and more preferably nitrogen. The temperature of the pulling growth is preferably 1500-1700°C, more preferably 1550-1600°C. In a specific embodiment, the temperature of the pulling growth is higher than xPr:AB 1-x The melting point of Ga3O7 polycrystalline raw material is about 50°C. The pulling speed is preferably 0.5-3 mm / h, more preferably 1-2.5 mm / h, and specifically preferably 1 mm / h. The rotation speed during the pulling growth process is preferably 5-15 r / min, more preferably 10-13 r / min. The rotation speed is the rotation speed of the pulled growing crystal sample.

[0056] In the present invention, an initial crystal is obtained after the pulling growth is completed. The present invention preferably further comprises: cooling the initial crystal from the pulling growth temperature to room temperature to obtain the Pr ion-doped gallate laser crystal material; the cooling rate is preferably 5 to 20°C / h.

[0057] The present invention provides the use of the Pr ion-doped gallate laser crystal material described in the above technical solution or the Pr ion-doped gallate laser crystal material prepared by the preparation method described in the above technical solution in laser output in the visible light band.

[0058] In the present invention, the laser output in the visible light band preferably includes the output of cyan laser, the output of orange laser and the output of red laser.

[0059] In the present invention, the Pr ion-doped gallate laser crystal material can achieve multiple laser outputs ranging from cyan to deep red light under 450nm blue light excitation.

[0060] In the present invention, the Pr ion-doped gallate laser crystal material is preferably used for the output of 470-500nm cyan laser, 590-620nm orange laser and 630-660nm red laser.

[0061] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0062] In the following examples, the room temperature fluorescence spectrum and fluorescence decay curve of the crystal were measured using a FLS980 fluorescence spectrometer produced by Edinburgh Instruments, with an excitation wavelength of 450 nm.

[0063] Example 1

[0064] This embodiment uses the Czochralski method to grow SrGd 0.99 The specific preparation process of Ga3O7:1%Pr crystal is as follows:

[0065] According to the chemical formula SrGd 0.99 The molar ratio of each substance in Ga3O7:1%Pr (1%Pr:SGGM) is accurately weighed Pr6O 11 , Sr2CO3, Gd2O3 and Ga2O3 were mixed and ground evenly, pressed into tablets, and synthesized in a muffle furnace at 1200℃ for 20h (the heating rate from room temperature to 1200℃ was 200℃ / h), taken out and ground again, mixed evenly, pressed into tablets, and synthesized at 1250℃ for 20h (the heating rate from room temperature to 1250℃ was 200℃ / h). The synthesized samples were loaded into a Φ55×50mm 3 The iridium crucible was placed in a pulling furnace and the pulling method was adopted. In a N2 atmosphere, the growth temperature was about 50°C higher than the melting point, the pulling speed was 1mm / h, and the crystal rotation speed was 10r / min. After the pulling growth was completed, the crystal was cooled to room temperature at a rate of 15°C / h, and a crystal with a size of Φ15×25mm was grown. 3 High-quality 1% Pr:SGGM crystals. After grinding and sieving, a portion of the crystal sample was tested for X-ray diffraction spectrum. The results are as follows: Figure 1 The results show that the doping of Pr ions does not affect the crystal structure.

[0066] Take a 1% Pr:SGGM crystal sample and test its spectral performance. The absorption spectrum results are as follows Figure 2 As shown in the figure, 1% Pr:SGGM crystal shows a strong absorption peak at 450nm with a half-peak width of 9.8nm. This shows that the crystal is very suitable for blue light LD and can be directly pumped by blue light LD. Figure 3 As shown, under 450nm excitation, there are four strong and broad emission peaks, namely cyan emission at 488nm, orange emission at 616nm, red emission at 646nm and deep red emission at 729nm. Figure 4 The fluorescence decay curve shows that the lifetime is 35.2μs, which is relatively fast compared with other Pr-doped laser crystals (including Pr:YAlO3, Pr:Y3Al5O 12 、Pr:SrAl 12 O 19 ), the fluorescence lifetime of 1% Pr:SGGM is longer, which means that the crystal has a larger laser threshold and is easier to achieve laser output.

[0067] Among them: the laser threshold of Pr:YAlO3 is 68.7×10 -20cm 2 μs,Pr:Y3Al5O 12 The laser threshold is 41.6×10 -20 cm 2 μs,Pr:SrAl 12 O 19 The laser threshold is 79.4×10 -20 cm 2 μs, and the laser threshold of 1% Pr:SGGM prepared in Example 1 is 103.84×10 -20 cm 2 μs.

[0068] In summary, the present invention utilizes the Czochralski method to grow Pr 3+ Ion-doped gadolinium strontium gallate laser crystal. In this crystal, Pr 3+ The ions act as activated ions and achieve 502nm cyan light emission, 616nm orange light emission, 708nm red light emission and 729nm deep red light emission under 450nm wavelength excitation.

[0069] Example 2

[0070] In this embodiment, CaLa is grown by the Czochralski method. 0.99 The specific preparation process of Ga3O7:1%Pr crystal is as follows:

[0071] According to the molecular formula CaLa 0.99 The molar ratio of each substance in Ga3O7:1%Pr (1%Pr:CLGM) is the accurately weighed Pr6O 11 , Ca2CO3, La2O3 and Ga2O3 were mixed and ground evenly, pressed into tablets, and synthesized in a muffle furnace at 1200℃ for 20h (the heating rate from room temperature to 1200℃ was 200℃ / h), taken out and ground again, mixed evenly, pressed into tablets, and synthesized at 1250℃ for 20h (the heating rate from room temperature to 1250℃ was 200℃ / h). The synthesized samples were loaded into a Φ55×50mm 3 The iridium crucible was placed in a pulling furnace and the pulling method was adopted. In a N2 atmosphere, the growth temperature was about 50°C higher than the melting point, the pulling speed was 1mm / h, and the crystal rotation speed was 10r / min. After the pulling growth was completed, the crystal was cooled to room temperature at a rate of 15°C / h, and a crystal with a size of Φ15×25mm was grown. 3 High-quality 1% Pr:CLGM crystals. After grinding and sieving, a portion of the crystal sample was tested for X-ray diffraction spectrum. The results are as follows: Figure 1 , the doping of Pr ions does not affect the crystal structure.

[0072] The laser threshold of 1% Pr:CLGM prepared in Example 2 is 258.328×10 -20cm 2 μs.

[0073] The absorption spectrum results are as follows Figure 5 As shown in the figure, 1% Pr:CLGM crystal shows a strong absorption peak at 450nm with a half-peak width of 11.6nm. This shows that the crystal is very suitable for blue light LD and can be directly pumped by blue light LD. The emission spectrum results are shown in Figure 6 As shown, under 450nm excitation, there are four strong and broad emission peaks, namely cyan emission at 488nm, orange emission at 612nm, red emission at 644nm and deep red emission at 729nm. Figure 7 This is the fluorescence decay curve. The lifetime is fitted to be 39.2μs. Compared with other Pr-doped laser crystals, the fluorescence lifetime of 1% Pr:CLGM is longer, which means that the crystal has a larger laser threshold and is easier to achieve laser output.

[0074] In summary, the present invention utilizes the Czochralski method to grow Pr 3+ Ion-doped lanthanum calcium gallate laser crystal. In this crystal, Pr 3+ ions as activated ions, under the excitation of a 450nm xenon lamp, cyan emission at 488nm, orange emission at 612nm, red emission at 644nm, and deep red emission at 729nm were achieved. The disordered structure of the crystal enhanced the Pr 3+ The crystal of the present invention can be used for laser output in the visible light band and has broad application prospects in the fields of scientific research, industrial manufacturing and military.

[0075] Example 3

[0076] According to the molecular formula CaLa 0.997 The molar ratio of each substance in Ga3O7:0.3%Pr (0.3%Pr:CLGM) is the accurately weighed Pr6O 11 , Ca2CO3, La2O3 and Ga2O3 were mixed and ground evenly, pressed into tablets, and synthesized in a muffle furnace at 1200℃ for 20h (the heating rate from room temperature to 1200℃ was 200℃ / h), taken out and ground again, mixed evenly, pressed into tablets, and synthesized at 1250℃ for 20h (the heating rate from room temperature to 1250℃ was 200℃ / h). The synthesized samples were loaded into a Φ55×50mm 3 The iridium crucible was placed in a pulling furnace and the pulling method was adopted. In a N2 atmosphere, the growth temperature was about 50°C higher than the melting point, the pulling speed was 1mm / h, and the crystal rotation speed was 10r / min. After the pulling growth was completed, the crystal was cooled to room temperature at a rate of 15°C / h, and a crystal with a size of Φ15×25mm was grown. 3 High-quality 0.3% Pr:CLGM crystals. After grinding and sieving, a portion of the crystal sample was tested for X-ray diffraction spectrum. The results are as follows: Figure 8 , the doping of Pr ions does not affect the crystal structure.

[0077] The emission spectrum results of the product prepared in this example are as follows Fig. 9 As shown, under 450nm excitation, there are four strong and broad emission peaks, namely cyan emission at 485nm, orange emission at 615nm, red emission at 644nm and deep red emission at 729nm. Fig.10 This is the fluorescence decay curve. The lifetime is fitted to be 29.1μs. A longer lifetime means that the crystal has a larger laser threshold and is easier to achieve laser output.

[0078] In summary, the present invention utilizes the Czochralski method to grow Pr 3+ Ion-doped lanthanum calcium gallate laser crystal. In this crystal, Pr 3+ ions as activated ions, under the excitation of a 450nm xenon lamp, cyan emission at 485nm, orange emission at 615nm, red emission at 644nm, and deep red emission at 729nm were achieved. The disordered structure of the crystal enhanced the Pr 3+ The crystal of the present invention can be used for laser output in the visible light band and has broad application prospects in the fields of scientific research, industrial manufacturing and military.

[0079] Example 4

[0080] In addition to the crystal products prepared in Examples 1, 2 and 3, the present invention also explores the optical properties of Pr ion-doped barium lanthanum gallate polycrystalline powder materials. The preparation method of Pr ion-doped barium lanthanum gallate polycrystalline powder materials in this embodiment is basically the same as that in Example 2, except that the types of elements and the Pr ion doping concentration (x value) are different, x=0.1%.

[0081] like Fig.11 and Fig.12 As shown, the polycrystalline powder material prepared in this embodiment has Pr 3+ The ions acted as activated ions, and under the excitation of a 450nm xenon lamp, cyan emission at 488nm, orange emission at 616nm, red emission at 646nm, and deep red emission at 729nm were achieved. The fluorescence decay lifetime was fitted to be 25.2μs, which was shorter than that of the crystals prepared in Examples 1 to 3.

[0082] Example 5

[0083] When exploring the laser performance of calcium lanthanum gallate and strontium gadolinium gallate, the present invention also explores the influence of different Pr ion concentrations on the laser performance according to the needs of laser operation, such as Fig.13 and Fig.14The performance of the Pr ion-doped lanthanum calcium gallate polycrystalline powder material (the preparation method of the Pr ion-doped lanthanum calcium gallate polycrystalline powder material in this embodiment is basically the same as that in Example 2, except that the doping concentration of the Pr ions is different), such as Fig.13 and Fig.14 As shown in the figure, with the increase of Pr ion concentration, the luminescence intensity of the polycrystalline powder material first increases and then decreases, and its intensity is the strongest when the Pr ion concentration is 5%. The fluorescence decay lifetime shows that with the increase of Pr ion concentration, the lifetime gradually decreases.

[0084] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A Pr ion-doped gallate laser crystal material, characterized in that: The chemical formula of the Pr ion-doped gallate laser crystal material is shown in Formula 1: xPr:AB 1-x Formula 1 of Ga3O7, In Formula 1, the A element is at least one of Ca, Sr and Ba, the B element is at least one of Y, La, Gd and Lu, and 0<x≤0.

2.

2. The Pr ion-doped gallate laser crystal material according to claim 1, characterized in that: The Pr ion-doped gallate laser crystal material belongs to the tetragonal system, and the space group is 3. The Pr ion-doped gallate laser crystal material according to claim 1 or 2, characterized in that: The A element is Ca or Sr, and the B element is Gd or La.

4. The method for preparing a Pr ion-doped gallate laser crystal material according to any one of claims 1 to 3, characterized in that: The following steps are involved: According to the chemical composition of the Pr ion-doped gallate laser crystal material, the prepared raw material is sintered twice to obtain xPr:AB 1-x Ga3O7 polycrystalline raw material; the two sinterings include a first sintering and a second sintering; In a protective gas atmosphere, the xPr:AB 1-x The Ga3O7 polycrystalline raw material is pulled and grown to obtain the Pr ion-doped gallate laser crystal material.

5. The preparation method according to claim 4, characterized in that: The preparation raw materials include praseodymium oxide, gallium oxide, carbonate containing element A and oxide containing element B.

6. The preparation method according to claim 4 or 5, characterized in that: The first sintering includes sequentially performing first grinding, first tableting and first calcining; The temperature of the first calcination is 1000-1300° C., the time is 15-25 hours, and the heating rate from room temperature to the temperature of the first calcination is 150-250° C. / h.

7. The preparation method according to claim 4 or 5, characterized in that: The second sintering includes sequentially performing a second grinding, a second tableting and a second calcining; The temperature of the second calcination is 1000-1300° C., the time is 15-25 hours, and the heating rate from room temperature to the temperature of the second calcination is 150-250° C. / h.

8. The preparation method according to claim 4 or 5, characterized in that: The pulling growth temperature is 1500-1700° C., the pulling speed is 0.5-3 mm / h, and the rotation speed is 5-15 r / min.

9. The preparation method according to claim 4 or 5, characterized in that: After the pulling growth is completed, an initial crystal is obtained, and the process also includes: cooling the initial crystal from the temperature of the pulling growth to room temperature to obtain the Pr ion-doped gallate laser crystal material; the cooling rate is 5 to 20° C. / h.

10. Use of the Pr ion-doped gallate laser crystal material according to any one of claims 1 to 3 or the Pr ion-doped gallate laser crystal material prepared by the preparation method according to any one of claims 4 to 9 in laser output in the visible light band.

Citation Information

Patent Citations

  • Erbium ion activated 1.55-micron wave-band gallate laser crystal and its preparation method

    CN102766905A

  • Thulium-holmium-codoped strontium lanthanum gallate laser crystal, preparation method and application of crystal

    CN105887200A

  • Dysprosium ion doped gadolinium lanthanum strontium aluminate yellow laser crystal and preparation method and application thereof

    CN118087042A

  • Monocrystalline lanthanum orthogallate laser material

    US4954211A